Investigating and Ranking Barriers to Strategic Implementation in Telecommunication Center of Tehran Province - Shirin Javaheri; Ahmad Abdolvand; Aghdam Mohammadloo (Ital Publication, 2018)
This study sought to investigate and rank the barriers to strategic implementation in Telecommunication Center in Tehran province. In terms of the objectives, it is an applied study and with regard to the methodology, it is descriptive as it describes the conditions of phenomena. The statistical population consisted of 140 managers, senior experts and elites of Telecommunication Center of Tehran province. Using Morgan's table, a total of 90 people were selected as the study sample. The instrument to collect the required data was a researcher-made questionnaire. The validity of the questionnaire was confirmed by the experts in the field and the reliability within the pilot study was 0.87. In this research, four barriers were raised including: system and management barriers, barriers related to employees, barriers to strategic planning, and barriers to non-allocation of resources.Investigating the capability of fitting the strategic barriers model in Telecommunication Center of Tehran province revealed that all the barriers were within the acceptable limits. In this study, content validity was assessed using expert judgment and construct validity using the confirmatory factor analysis. The TOPSIS technique was then run to prioritize the barriers. Findings indicate that whereas the system and management barriers have the highest rank, the barriers related to employees have the lowest rank.